HUBUNGAN MOTIVASI BELAJAR DENGAN HASIL BELAJAR PENJASORKES DI SMAN 1 GUNUNG TOAR PADA MASA PANDEMI COVID 19 - Syafrico, Kiki; Juita, Ardiah; Sulastio, Agus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: The aim of this research is to determine the relationship betweenlearning motivation and Physical Education learning outcomes for Class XI SMAN 1Gunung Toar during the Covid-19 pandemic. This research took place at SMAN 1Gunung Toar Jl. Jenderal Sudirman KM 3, Petapahan, Gunung Toar District, Kab.Kuantan singi. The time of the research was carried out in July 2021 - January 2023.Based on data analysis, as well as discussion of the research results, the followingconclusions can be drawn: There is a significant relationship between learningmotivation and student learning outcomes in Physical Education subjects at SMANegeri 1 Gunung Toar Kuantang Singingi with Rcount = 0.406 and r table 0.367. Theresults obtained by r calculated are based on the correlation coefficient interpretationtable, then the correlation coefficient obtained is at a strong level. This shows thatstudent learning motivation has a strong relationship with student learning outcomes inphysical education subjects at SMA Negeri 1 Gunung Toar, Kuantang SingingiRegency.Keywords: The Relationship between Learning Motivation and Learning Outcomes